KARAKTERISTIK POLA PENGHASILANPENYEDIA BARANG DAN JASADI KAWASAN PENDIDIKAN TINGGI JATINANGOR - M Bobby Rahman (Diponegoro University, 2016)
Jatinangor as the area of higher education for the five colleges appeals to the emergence of trade and services around campus locations. This study discusses the characteristics of the pattern of trade and services revenue that arises due to the influence of the activities of the academic community in the area. The data collection methods are questionnaire technique and secondary data collection. The questionnaires were distributed to the suppliers of goods and services. The analytical method used is descriptive analysis. The results indicate the influence of the academic community, especially students so that the income of providers of goods and services is relatively high. A significant influence on the pattern of income of the services providers is by the active time-off lectures and domicile of the academic community. The percentage of influence reached 59% in terms of decline turnover experience.